A fedezeti elv és a becsérték az adóvégrehajtás rendszerében - Darai, Péter (Debreceni Jogi Műhely, 2019)
In my essay I’m trying to answer some questions in the topic of the appraisal of real property. During my work – in National Tax and Customs Administration of Hungary – I daily meet the problem that the process of appraisal is very complex activity because of many internal and external factors. It needs great attention because the appraised value influences the execution of movable and immovable property and determines the purchase price in compulsory auctions. With this in mind it effects on refundation of tax debt. It is important to note at the same time that the target of the execution is not the recovery of the debt at any cost; at least essential guaranteed procedures which protect the rights of the debtors. In the following lines I focus the operative legislation of the tax execution proceeding and I describe the concerning judicial precedent with particular attention te case law of the Supreme Court. The importance of the subject presented by some decisions of the Constitutional Court. In my opinion without exaggeration the theme is so interesting the recently changed legislation cannot be connected to it because in theory anyone can get into a life situation that execution proceeding so it is worth knowing some rules about it.